A NEW "EDITION" OF ḤUNAYN'S RISĀLA. Issue 2 (10th August 2018) - Gutas, Dimitri
Abstract : One of the most important medieval documents in the history of medicine and scholarship, and of culture in general, is doubtless the bibliographical treatise ("epistle", Risāla ) by Ḥunayn b. Isḥāq (808-873) addressed to his patron and patron of the arts, the gentleman courtier 'Alī b. Yaḥyā b. al-Munaǧǧim (d. 275 / 888-889), listing the translations of Galen into Syriac and Arabic. Its transmission and publication history, though, is extremely complicated.